Pengaruh capital adequacy ratio, debt to equity ratio, dan ukuran perusahaan terhadap profitabilitas Bank Umum Syariah di Indonesia: Peran islamic social reporting sebagai pemoderasi - Ningtyas, Yunita; Pratama, Abdul Aziz Nugraha (Nur Science Institute, 2022)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Debt To Equity Ratio (DER), and Firm Size on Profitability (ROA) with Islamic Social Reporting (ISR) as a moderating variable. This type of research is quantitative research with secondary data in the form of panels. The population in this study were 14 Islamic Commercial Banks in Indonesia for the 2016-2020 period. Sample selection using purposive sampling method. The analytical technique used is multiple linear regression analysis. The results of this study found that the Capital Adequacy Ratio (CAR) and Debt To Equity Ratio (DER) had a negative and insignificant effect on profitability. However, Firm Size has a negative and significant effect on profitability (ROA). Islamic Social Reporting (ISR) does not moderate the effect of Capital Adequacy Ratio (CAR) and Debt To Equity Ratio (DER) on profitability (ROA). However, it moderates the Firm Size variable on profitability (ROA).